Методичні основи розробки стандарту визначення енергоємності комбінованого виробництва електричної енергії і теплоти на електричних станціях - Dubovskoy S.V.; Khortova О.А. (General Energy Institute of the National Academy of Sciences of Ukraine, 2009)
The theoretical features of calculation of specific expense of fuel on electric and heat energy supply are considered for the serial steam extraction turbine by a thermodynamics method. The dependences on the initial and eventual parameters of working process of basic indexes of energy efficiency was explored for such aggregates and as a result of an empiric formula is shown out.